YciR, a Specific 3′-Phosphodiesterase, Plays a Role in the Pathogenesis of Uropathogenic Escherichia coli CFT073 - Zhang, Si; Wang, Jingting; Fan, Yu; Meng, Wang; Qian, Chengqian; Liu, Peng; Wei, Yi; Yuan, Chao; Du, Yuhui; Yin, Zhiqiu (Frontiers in Microbiology, 2022)
Urinary tract infections (UTIs), with the characteristics of recurrence and resistance to antibiotics due to misuse, remain a common health and economic issue for patients. Uropathogenic Escherichia coli (UPEC), which is capable of evading the immune response by forming intracellular bacterial communities (IBCs) in the cytoplasm of bladder epithelial cells (BECs) after invasion, has been shown to be the prevailing cause of UTIs. Cyclic dimeric guanosine monophosphate (c-di-GMP) is a small molecule responsible for eliciting the innate immune response of the host only if it has not been degraded by some phosphodiesterases (PDEs), such as YciR. The relationship between YciR and c-di-GMP levels in UPEC is inconclusive. In this study, we investigated the gene expression profile of UPEC in BECs and identified yciR as an upregulated gene. Western blot revealed that YciR enhanced the virulence of UPEC by inhibiting the phosphorylation of NF-κB. The expression of yciR could be repressed by HupB in a directly binding manner. We identified YciR, a novel PDE, and defined its possible function in innate immune evasion. We also demonstrated that YciR is an HupB-dependent PDE that degrades c-di-GMP and that a low concentration of c-di-GMP might make NF-κB less phosphorylated, thereby reducing the host’s pro-inflammatory response. This is the first time that YciR has been identified as a virulence factor in the pathogenesis of UPEC. These findings further increase our understanding of the pathogenesis of UPEC and provide a theoretical basis for further studies.